Noise temperature and gain loss due to paints and primers a case study of DSN antennas. - Otoshi, T.Y (IEEE Antennas & propagation magazine.)
In achieving high performance for reflector antennas, it has been noted that it is essential to carefully assess the roles of surface paints and primers. A thorough literature search has revealed that not much has been reported on this very important engineering-implementation topic. It is one of the main objectives of this feature article to provide a detailed study on the effects of paints and primers on reflector-antenna performance. In particular, as a case study, this paper presents excess-noise-temperature and added-gain loss data at 32 GHz for various combinations of paints and primers currently being studied for use on DSN (Deep Space Network) antenna reflector surfaces. It is shown that 500FHR6 acrylic urethane-based paint has the lowest excess-noise-temperature contribution. Previously, it has been recommended that this paint be used for all new DSN beam-waveguide antennas being constructed, and for all those 34-m and 70-m antennas with reflector surfaces that need repainting. The results, methodologies, and observations presented in this article are also applicable to other reflector-antenna configurations.